A CURRICULUM DESIGN FOR EDUCATING CONSERVATORS OF ISLAMIC MANUSCRIPTS - Hepworth, Paul; Scheper, Karin; Barkeshli, Mandana (PLANNING MALAYSIA, 2017)
To meet the pressing need for more training for conservators in developing countries dealing with Islamic manuscripts, a curriculum design was prepared. This details the skills and information needed and organizes instruction into modules that can be taught as a total program or semiindependently with adaptation to many different circumstances in different settings. The modules are augmented by specified objectives, possible instructional activities and assessment strategies.